Jezuickie kolegia szlacheckie w Europie Zachodniej. Rekonesans - Puchowski, Kazimierz (Horyzonty Wychowania, 2017)
This article presents the establishment and development of Jesuit colleges for nobility in Western Europe. The activity of these schools expressed consideration for the elite’s educational aspirations in the order policy. Private boarding schools, serving a selected group of young people, in terms of ideology, organization as well as programme, constituted a certain anomaly in Jesuit educational system. They were also an expression of the selective approach to egalitarianism propagated in Konstytucje Towarzystwa Jezusowego (The Constitutions of the Society of Jesus) and Ratio studiorum (1599). Responding to the educational aspirations of the upper classes, Jesuits were reforming secondary school. Selective implementation of elements of the programme and methods adopted in knight’s academies did not shake the foundations of humanistic tradition, but the aim of the institutions for nobility was essentially different from the one ascribed to knight’s academies. Jesuits wanted to shape their students devoted to Church and at the same time strengthen the order’s influence among clerical and lay elite. The initiative regarding establishment of schools for elite involved mainly kings, whose aspiration was that exclusive schools educate competent people devoted to monarchy. School founders – monarchs and princes presented their own aspirations and demands to the order, thus individual colleges had their own flavour in terms of organization and programme. The author of the article indicates that despite popular opinion in Polish historiography, Jesuits, and not Piarists were the first to modify secondary schools and establish collegia nobilium. Jesuits understood that running such institutions for aristocrats’ sons (in France also for the sons of wealthy burgesses) offers an opportunity to take over a certain strategic function, that is control over education of those who would assume power in the centralizing state.